Handbook of European Union Politics (Sage Publications, 2006)
The European Union (EU) poses quite profound questions for scholars and students of the social and political sciences. This benchmark Handbook is designed to provide an authoritative state-of-the art guide to the scope of the field suitable for both established scholars and students of the EU; reflect and contribute to the debates about the nature of the field of EU studies and EU politics in particular; and explore in detail the development of the many approaches to the study of EU politics. Divided into four sections, the Handbook focuses on theorizing European integration; the EU as polity; politics and policy making in the EU; and the EU and the international system.